Predictable and non-stationary processes of interval PREDICTION BASED ON stochastic differential equations - A. V. Ausiannikau (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The task of interval prediction of non-stationary processes of stochastic differential equations described by models is considered. Predictability of such processes is defined. Algorithms of interval prediction in the discrete and continuous time are received.